Technological progress with segmented factor markets and welfare implications for the urban poor - Soumyatanu Mukherjee; Sameen Zafar (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2015)
Motivated by a set of stylised facts based on provincial data for India, this paper investigates the incidence of urban poverty by modelling the impact of technological progress in the formal sectors of the economy on the urban informal wage in a four-sector general equilibrium framework with labour and capital market distortions. Uniform technological progress only in the capital intensive segment of the formal sectors affects the urban informal workers adversely, whereas productivity improvement only in the less capital intensive sector benefits them. The sensitivity analysis demonstrates that when both formal sectors undergo uniform technological progress at the same rate, informal wage may improve if the vertically integrated sector is less capital intensive (as capital flows to the informal sectors). This helps in understanding trends in urban poverty given the strong association between the urban informal wage and degree of urban poverty.
Keywords: E26; F11; F16; J46; I32; O17; 330; Poverty; Technological Progress; Informal Wage; General Equilibrium